Report of the 2013 University of Puerto Rico- MD Anderson Cancer Center Conference entitled “Research on Cancer Epidemiology: Risk Factors and Control in the Caribbean Basin” - Suárez, Erick; Soto-Salgado, Marievelisse; Moreno-Gorrín, Camille; Ortiz, Ana Patricia; Pérez, Cynthia M. (Puerto Rico Health Sciences Journal, 2014)
An interdisciplinary conference entitled “UPR-MDACC 2013 Research on cancer epidemiology: risk factors and control in the Caribbean basin” was held on February 21-22, 2013 at the Verdanza Hotel in Isla Verde, Puerto Rico. The Biostatistics and Bioinformatics Core (BBC) of the Partnership for Excellence in Cancer Research Program between the University of Puerto Rico (UPR) and the MD Anderson Cancer Center (MDACC) organized this conference. The purpose of this conference was to establish the foundation for a network of collaboration and support in cancer research in the Caribbean basin, particularly in those regions with limited resources. This conference included 16 presentations in four sessions over two days. Overall, 100 participants attended this conference. According to an external evaluation, the speakers’ presentations fully met the conference goals and the expectations of the participants. Some of the lectures offered are available on the Internet. In conclusion, this conference helped to lay the groundwork for development of a comprehensive research agenda to address methodological issues in cancer-related research among Caribbean countries.